Ecological Analysis of Preeclampsia/Eclampsia Case in Sidoarjo Regency, Indonesia, 2015-2019 - Sesotiyaningsih Madiyaning Utami1 , Farida Handayani1 , Mam (Indian Journal of Forensic Medicine & Toxicology, 2020)
Preeclampsia is hypertension that arises after 20 weeks of pregnancy accompanied by proteinuria, thesymptoms are divided into mild and severe preeclampsia. Preeclampsia with a coma is called eclampsia.Globally 80% of maternal deaths are classified as direct death. Hypertension is directly responsible forapproximately 20% of maternal deaths in the United States. Supas in 2015 showed maternal mortality ratein Indonesia 305/100,000 live births and the highest in Southeast Asian countries which only 40-60/100,000live births. One of the main causes is preeclampsia/eclampsia. In Sidoarjo Regency in the last 5 years, themost common cause of maternal death was preeclampsia/eclampsia by 58%. The purpose of this study wasto determine the description of the incidence of preeclampsia/eclampsia in the last 5 years in the SidoarjoRegency. This research is a descriptive study with a quantitative approach using secondary data from theSidoarjo District Health Profile in 2015-2019. The results found that the highest incidence of preeclampsia/eclampsia in the Sidoarjo Regency was Temple Health Center and Taman Health Center (5.74%), andBuduran Health Center (4.10%). The trend in the incidence of preeclampsia/eclampsia in the SidoarjoRegency over the past 5 years has fluctuated and has not shown a better change. It could be concludedthat there are 3 Health Centers that have the highest percentage of preeclampsia/eclampsia due to lack ofknowledge about maternal health. This shows that the program carried out by the Government to reduce theincidence of preeclampsia/eclampsia in the Sidoarjo Regency has not been effective so further interventionis needed.